2002
DOI: 10.1165/rcmb.4710
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Inhibit Lung Cancer Cell Growth through Both the Extracellular Signal-Related Kinase Pathway and Cell Cycle Regulators

Abstract: Glucocorticoids inhibit the proliferation of various cell types, but the mechanism of this inhibition remains unclear. We investigated the effect of dexamethasone on non-small cell lung cancer cell growth and cell cycle progression. We showed that dexamethasone suppresses the proliferation of A549 and Calu-1 cells, with accumulation of cells in G1/G0 stage of the cell cycle, as determined by fluorescence-activated cell sorter analysis. Western blot analysis confirmed that this is associated with hypophosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 52 publications
9
66
0
4
Order By: Relevance
“…Again, this matches the regional specification of deficits of neural cells after DEX administration as reported for treatment in vivo (Bohn, 1984;Kreider et al, 2005aKreider et al, , 2006, reinforcing the likelihood that these, too, represent direct effects of DEX on the developing brain. Furthermore, DEX arrests mitotic activity at the G 0 /G 1 phase (Greenberg et al, 2002), which contributes to its therapeutic effect in the immature lung, switching pneumocytes from replication to differentiation and thus promoting surfactant production (Gross, 1990). Given the same mechanism, but a lower concentration threshold for effects on neural cell division, this finding reinforces the idea that therapeutic use of glucocorticoids aimed at lung maturation will also target the developing brain.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Again, this matches the regional specification of deficits of neural cells after DEX administration as reported for treatment in vivo (Bohn, 1984;Kreider et al, 2005aKreider et al, , 2006, reinforcing the likelihood that these, too, represent direct effects of DEX on the developing brain. Furthermore, DEX arrests mitotic activity at the G 0 /G 1 phase (Greenberg et al, 2002), which contributes to its therapeutic effect in the immature lung, switching pneumocytes from replication to differentiation and thus promoting surfactant production (Gross, 1990). Given the same mechanism, but a lower concentration threshold for effects on neural cell division, this finding reinforces the idea that therapeutic use of glucocorticoids aimed at lung maturation will also target the developing brain.…”
Section: Discussionsupporting
confidence: 54%
“…Each neural cell contains only a single nucleus (Winick and Noble, 1965), so that the DNA content reflects the total number of cells (Song et al, 1998); since DEX arrests mitosis in the G 0 /G 1 phase (Greenberg et al, 2002), this relationship holds true even where DEX treatment affects cell acquisition. Indices of growth were provided by measurements of protein subfractions related to cell size and membrane surface area (Thai et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For determining receptormediated signaling, treatments were limited to 15 min; for measuring induction of genes, altered cell morphology, or change in cell cycle markers, the treatments ranged from 24 to 48 h. To determine cell proliferation, the cells were seeded at 1% density into 24-well culture plates. After 24 h, the medium was replaced by fresh, serum-containing medium that also included 10-fold serially diluted cytokines or dexamethasone (34). After 3 days, the culture medium was replaced, and another 3 days later, the number of viable cells in each well was counted in a hematocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…4B). For evaluating the effectiveness of IL-6 cytokines in promoting growth arrest, treatment with dexamethasone was included because of the known potent action of the steroid in arresting epithelial cells in G 1 (34). The comparison of parental and IL-31R␣-transduced A549 cells indicated that IL-31 strongly suppressed proliferation with an IC 50 of ϳ0.2 ng/ml.…”
Section: Il-31r␣-transduced A549 Cells As Model To Define Il-31 Actiomentioning
confidence: 99%
“…Their actions appear to go beyond the anti-inflammatory effects and have been shown to include inhibition of lung cancer cell growth and regulation of cell cycle (27) and chemosensitization of other cytotoxic anti-cancer drugs (28). Considering the inflammatory and proliferative roles of prostaglandins, we examined the effect of glucocorticoids on the induction of 15-PGDH expression in A549 cells.…”
Section: Glucocorticoids Induce 15-pgdh Expressionmentioning
confidence: 99%